Inhibitory influence of amino acids on the formation kinetics of methane hydrates in oil-water and oil-brine systems - Almashwali, A.A. (2023)
This experimental study evaluates the inhibition performance of kinetic hydrates inhibitors (KHIs) of three amino acids, namely: glycine, proline, and alanine. It includes the performance comparison with the conventional inhibitor i.e., polyvinyl pyrrolidine (PVP) on methane (CH4) hydrate in oil systems in two different systems, i.e., deionized and brine water systems. The experiments were conducted in a high-pressure hydrate reactor replicating subsea pipeline conditions, i.e., the temperature of 274 K, pressure 8 MPa, and concentration of 1 wt, by applying the isochoric cooling technique. The formation kinetics results suggest that all the studied amino acids effectively worked as kinetic inhibitors by potentially delaying CH4 hydrate formations due to their steric hindrance abilities. The interesting phenomenon was observed that the different studied amino acids behave differently in the brine-oil and deionized water-oil systems due to their side chain interaction. In a deionized water-oil system, glycine gives the highest inhibition performance by reducing the hydrate formation risk. On the contrary, in the brine-oil system, proline showed a significant inhibition effect. It should be noted that both glycine and proline were giving almost similar inhibition performance compared to the conventional hydrate inhibitor PVP, however glycine and proline significantly reduced CH4 consumption into hydrate due to their high surface active under CH4 conditions, which strengths the surface tension of the liquid/CH4 interface. Furthermore, according to the findings, it shows that increased side alkyl chain lengths of amino acids increase the efficacy of their kinetic hydration inhibition performance due to better surface adsorption abilities. The amino acids' ability to suppress growth is also linked strongly with hydrophobicity and alkyl side chain length. The findings of this study contribute significantly to current efforts to limit gas hydrate formation in offshore pipelines, particularly in oil-dominant pipelines. Â© 2022 Elsevier Ltd